Recurrent parathyromatosis in a patient with concomitant MEN1 and CASR gene alterations: Clinical management of a case report and literature review - Sapuppo, Giulia; Giusti, Maria Ausilia; Aricò, Demetrio; Masucci, Romilda; Tavarelli, Martina; Russo, Marco; Pellegriti, Gabriella (Frontiers in Endocrinology, 2023)
Introduction: Parathyromatosis is a rare cause of primitive hyperparathyroidism characterized by the presence of numerous parathyroid tissue foci in the neck/mediastinum, due to hyperplasia of parathyroid embryologic residues (primary-form) or to local parathyroid tissue implantation (secondary-form). 63 cases have been described in the literature. In our patient parathyromatosis was due to a combination of two mutations. Case report: A 36-years-old woman was diagnosed with osteoporosis secondary to primary hyperparathyroidism. Subsequent right parathyroidectomy showed a parathyroid adenoma. The follow-up was negative but after 10 years she had a relapse. The genetic screening showed a rare intronic mutation of the MEN1 gene and a heterozygous mutation never described in exon 8 of the CASR gene, coding for the calcium receptor. Calcemia and PTH increased over the years with the onset of nephrocalcinosis and the worsening of osteoporosis despite the therapy with Cinacalcet, bisphosphonates and Vitamin D. She had therefore two additional surgical procedures (parathyroid tissue without malignancy). At follow-up she showed elevated levels of PTH (>1000 pg/ml) and calcium (11.2 mg/dl) and CT scans multiple subcentimetric nodules in the neck/upper mediastinum. Since the ⁶⁸Ga-DOTATATE showed an increased uptake in the neck/mediastinum, lanreotide was added. After two months there was a significant biochemical response but, unfortunately, after six months, the patient showed a new worsening. Conclusions: a rare case of parathyromatosis due to a combination of two genetic alterations never described. The main issues concern the diagnosis and the radical treatment. Somatostatin analogues may have a useful role in both diagnosis and therapy.